2014
DOI: 10.1128/jcm.02695-13
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Pneumococcal Serotype 11A Variants Results from Incomplete Loss of Capsule O -Acetylation

Abstract: Streptococcus pneumoniae is a significant bacterial pathogen that expresses >90 capsule serotypes. Conventional serotyping methods assume that each serotype is a genetically and antigenically distinct entity; however, recent investigations have revealed pneumococcal isolates that cannot be unambiguously serotyped because they share the properties of more than one serotype. Here, we employed a novel serotyping method and NMR spectroscopy to examine clinical isolates sharing properties of serotypes 11A and 11E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…The serotype 20A strain (AMB11) and serotype 20B strain (AMB12) were generated using ATCC 6320 (American Type Culture Collection, Manassas, VA) and CDC5931-06 (Centers for Disease Control and Prevention, Atlanta, GA), respectively, by introducing a streptomycin resistant rpsL allele using a previously described method (13). The wcjE-null strains AMB13 (serotype 20Ax) and AMB14 (serotype 20Bx) were generated from strains AMB11 and AMB12, respectively, using a previously described protocol (14). Saccharomyces cerevisiae used for MBL binding assays was a kind gift from the laboratory of Stephen Moser at the University of Alabama at Birmingham (Birmingham, AL).…”
Section: Methodsmentioning
confidence: 99%
“…The serotype 20A strain (AMB11) and serotype 20B strain (AMB12) were generated using ATCC 6320 (American Type Culture Collection, Manassas, VA) and CDC5931-06 (Centers for Disease Control and Prevention, Atlanta, GA), respectively, by introducing a streptomycin resistant rpsL allele using a previously described method (13). The wcjE-null strains AMB13 (serotype 20Ax) and AMB14 (serotype 20Bx) were generated from strains AMB11 and AMB12, respectively, using a previously described protocol (14). Saccharomyces cerevisiae used for MBL binding assays was a kind gift from the laboratory of Stephen Moser at the University of Alabama at Birmingham (Birmingham, AL).…”
Section: Methodsmentioning
confidence: 99%
“…70 Subsequent structural and molecular analysis revealed that S. pneumoniae types 11E and 11A represent the two extremes of a population comprising variants, which differ by the activity of the wcjE 10 gene, and consequently by the level of expression of a 6-O-acetyl-β-D-Galp residue in their CPS repeating unit. 69 The molecular mechanisms responsible for restraining the wcjE function are not yet elucidated.…”
Section: This Journal Is © the Royal Society Of Chemistry [Year]mentioning
confidence: 99%
“…88 The occurrence of intermediate serovariants as in systems 11A/11E and 9A/9V was hypothesized. 69 In this context, the effect of CPS O-acetylation on functional antibody activity and potential cross-reactivity was questioned. A measurable antigenic difference between CPSs from type 15B and type 15C was shed to light by use of sera from individuals O-acetylation was substantiated by the absence of functional antibodies cross-reacting with type 15C in post-vaccination sera.…”
Section: -85 30mentioning
confidence: 99%
See 1 more Smart Citation
“…Many bacteria have membrane-bound O-acetyltransferases (MOATs) that are thought to attach O-acetyl groups to the capsular repeat unit at the end of the capsular biosynthetic process (22)(23)(24). Accordingly, the loss of MOAT-mediated O-acetylation may not disrupt global capsule biosynthesis (12,(25)(26)(27).…”
mentioning
confidence: 99%